2020
DOI: 10.25082/ccr.2020.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Financial distress among breast cancer survivors

Abstract: Aims: there has been an increasing awareness of the potential for oncology care to result in long-term financial burdens and financial toxicity. Patients who report cancer-related financial problems or high costs are more likely to forgo or delay prescription medications and medical care. Materials and Methods: we examined financial distress using data from a survey of 164 breast cancer survivors who had completed primary therapy for the disease. Key Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Some physicians in our study agreed that the lower cost of biosimilars would likely result in improved access to cancer treatment with biologics. It is well-established that cancer-related financial toxicity (CRFT) is associated with an increased risk for medical noncompliance and delayed prescription refills and critical care, which can negatively affect clinical outcomes [34][35][36]. The introduction of biosimilars may help mitigate CRFT in patients with cancer [37].…”
Section: Discussionmentioning
confidence: 99%
“…Some physicians in our study agreed that the lower cost of biosimilars would likely result in improved access to cancer treatment with biologics. It is well-established that cancer-related financial toxicity (CRFT) is associated with an increased risk for medical noncompliance and delayed prescription refills and critical care, which can negatively affect clinical outcomes [34][35][36]. The introduction of biosimilars may help mitigate CRFT in patients with cancer [37].…”
Section: Discussionmentioning
confidence: 99%
“…4 Breast cancer is one of the major health burdens in Indonesia. The burdens are different exposures to risk factors, economic settings, lifestyles, access to care and screening, 5 delay in seeking help and non-adherence 6 , financial toxicity, 7,8 , and Social Insurance Administration Organization reported that from 1,308,061 inpatient cancer cases treated in 2016, a total of 2.2 trillion rupiahs was spent, amounting to $486,960,633 in the US dollars (purchasing power…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, in view of the fact that there is no good strategy to cure cancer completely at present, the post-operative care and rehabilitation of cancer patients, the burden of patients' families and the social care measures for cancer patients have undoubtedly become the forefront and hotspot of contemporary cancer prevention and treatment research. Coughlin et al shared their series of original explorations on the related topics in these respects [1][2][3][4][5][6]. Mori et al explored the interactions between HIF and COX-2 with chemotherapeutic agents under normoxia and hypoxia with breast cancer cell MDA-MB-231 and SUM-149 as in vitro cell models under the background of 5-FU treatment, tried finding the potentials of COX-2 inhibitors for enhancing the therapeutic effects of 5-FU on triple negative breast cancer (TNBC), a subgroup of breast cancer lacking the expression of estrogen and progesterone receptors as well as HER2 [7].…”
mentioning
confidence: 99%